Study of relationship between hearing loss and Obesity - دلا ريم; يوسف يوسف; مصطفى ابراهيم (Latakia University Journal -Medical Sciences Series, 2023)
Objective: Hearing loss is a highly prevalent chronic condition in adults, which is associated with significant effects on communication, productivity and altered quality of life. Of emerging interest is that obesity may precipitate development of hearing loss. The aim of this study was to determine the association between body mass index(BMI) and development of sensorineural hearing loss. Materials and methods: An Observational Descriptive study (case series) conducted for the period one year (2021- 2022) at Tishreen University Hospital in Lattakia-Syria. The study included all patients who visited Otolaryngology clinic with various complaints and underwent to hearing screening tests, patients were divided according to presence of hearing loss, and relationship between prevalence and severity of hearing loss with BMI was analyzed. Results: Out of 163 cases, sensorineural hearing loss was present in 87 cases. There were significant differences between two groups regarding age in which patients with hearing loss were older (46.1±8.2 versus 40.5±6.3, p:00.02). Mild hearing loss represented the most frequent form (60.9%) followed by moderate (25.3%) and severe (13.8%). There were significant differences between two groups regarding BMI in which hearing loss was more frequent in overweight (18.7%) and obese patients (36.7%) compared to underweight (13.9%) and normal (20.7%), p:0.01. Presence of obesity was associated with the risk of hearing loss OR:1.8[1.1-9.2], p:0.03. Conclusion: The current study demonstrated that increasing weight was associated independently with development of hearing loss.